Identification of Invertebrate Species in the Coastal Area of Labuhan Lalar Village, West Sumbawa Regency - Aulia, Jamiatul; Seprianingsih, Dewi; Sahratullah, Sahratullah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Coastal biodiversity plays a crucial role in maintaining the stability and productivity of marine ecosystems. Among the key contributors to these systems are marine invertebrates, particularly molluscs and crustaceans, which fulfil important ecological functions such as nutrient cycling, water filtration, and forming part of the marine food web. However, scientific data on the diversity of marine invertebrates in many Indonesian coastal regions remains limited, especially in remote areas like Labuhan Lalar Village, West Sumbawa Regency. This study aims to identify and classify marine invertebrate species found along the coast of Labuhan Lalar. An exploratory research approach was applied through direct field surveys along the shoreline, using a 3-meter transect from the high tide line toward the sea. Invertebrate specimens were collected manually and identified based on external morphological characteristics. A descriptive analysis was conducted with reference to scientific literature to determine species classification. The research identified a total of 15 marine invertebrate species belonging to two major phyla: Mollusca and Arthropoda. These species were further grouped into three classes: Gastropoda (10 species), Bivalvia (4 species), and Malacostraca (1 species). The presence of these diverse taxa indicates that the coastal ecosystem of Labuhan Lalar remains ecologically functional and supports a variety of marine invertebrate life. In conclusion, the coastal area of Labuhan Lalar demonstrates a relatively high level of marine invertebrate biodiversity. These findings may serve as baseline data for future biodiversity monitoring, conservation planning, and the development of sustainable coastal management strategies in the region.